2006
DOI: 10.1111/j.1095-8312.2006.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carotenoid and food availability on resistance to a naturally occurring parasite (Gyrodactylus turnbulli) in guppies (Poecilia reticulata)

Abstract: Dietary carotenoids have been shown to confer immunological benefits to some species of animals in which males also use these pigments to attract mates. Thus, the potential exists for an allocation trade-off between the sexual and immunological functions of carotenoids. Food availability may also influence immune system function. The present study examined the effects of carotenoid and food availability on the resistance of male guppies ( Poecilia reticulata Peters) from four wild populations to the parasite G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 55 publications
9
76
2
Order By: Relevance
“…For this study, the males from each of four sites (two low-and two high-food-availability) were raised on one of two food levels, low or high. Comparison of the asymptotic sizes of wild-caught males from low-and high-food-availability sites with males from the lab food treatments demonstrated that the low food level is on the low end of the range that guppies typically experience in the wild and the high food level is in the middle of the range (Kolluru et al 2006). The methods for behavioral observations were identical to those employed in the common garden experiment.…”
Section: Lab Behavior Observationsmentioning
confidence: 98%
“…For this study, the males from each of four sites (two low-and two high-food-availability) were raised on one of two food levels, low or high. Comparison of the asymptotic sizes of wild-caught males from low-and high-food-availability sites with males from the lab food treatments demonstrated that the low food level is on the low end of the range that guppies typically experience in the wild and the high food level is in the middle of the range (Kolluru et al 2006). The methods for behavioral observations were identical to those employed in the common garden experiment.…”
Section: Lab Behavior Observationsmentioning
confidence: 98%
“…Their essential role in immune function is attributed to their immunostimulating and immunoregulating effects (Blount et al, 2003;McGraw and Ardia, 2003;Saino et al, 2003;Grether et al, 2004;Peters et al, 2004;Cucco et al, 2006;Kolluru et al, 2006;McGraw et al, 2006;Aguilera and Amat, 2007). The concentration and the availability of carotenoids in the peripheral blood are often negatively related to parasite infestation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have confirmed that males with greater access to carotenoids have more colourful ornamental displays, better antioxidant defences and can mount larger immune responses (e.g. Blount et al 2003;McGraw & Ardia 2003;Kolluru et al 2006;Kurtz et al 2006; but see Navara & Hill 2003). However, evidence of a link between carotenoid supply and adult survival has so far been correlational (Hill 1991;Hõrak et al 2001) and no previous study has explicitly tested how carotenoid supply may influence resistance to senescence or longevity, and how these competing demands affect their ability to allocate carotenoids to sexual signals.…”
Section: Introductionmentioning
confidence: 99%